1907 N.H. Laws 142 - (:unkn) unknown (My University, 1907)
An Act Relating to the Committing of Burglary with Explosives, ch. 146, §§ 1-4: Provided that any person who breaks and enters a building with gunpowder, nitroglycerine, dynamite, or other explosives and commits burglary will be deemed guilty of burglary with explosives
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME